One in the Hand Worth Two in the Bush? Reproductive Effort of Young Males Is Not Affected by the Presence of Adult Males - Monteith, Kevin L.; Monteith, Kyle B.; Jenks, Jonathan A.; Jakopak, Rhiannon P. (Frontiers in Ecology and Evolution, 2020)
Reproduction is a costly endeavor, and most large, long-lived, and iteroparous mammals exhibit conservative life-history tactics wherein an individual may forego or abandon a reproduction event for the sake of survival. Nevertheless, risks and benefits associated with reproduction are not equal across males and females, nor across their life. Whereas expenditure for females is associated with rearing young (e.g., lactation), expenditure for males occurs with securing mating opportunities. Young males may be more successful when dominant males are lacking, but it is less clear whether—and at what cost—young males will expend effort when those opportunities arise. We designed an experiment to quantify reproductive effort (e.g., food intake, somatic loss [body mass and fat]) of male white-tailed deer (Odocoileus virginianus) to better understand the reproductive ecology of male ungulates, with an emphasis on determining how adult males (≥4.5-years old) affect timing and extent of reproductive effort expended by yearling males (1.5-years old). Food intake, hormone levels, body mass, and somatic loss during rut were similar between yearling males that interacted with adult males and those that did not. Somatic loss by all males was greatest during peak estrus of females, but forage intake relative to metabolic body mass for yearling males was nearly twice that of adult males. Testosterone levels were lower for yearling than adult males early in rut and were related negatively to forage intake. Whereas adult males lost 20% (23.5kg) of body mass and 31% (5.3 percentage points [ppt]) of body fat during the rut, yearling males lost 12% (9.3kg) of body mass and 22% (4.7ppt) of body fat. Reproductive effort by young males was not influenced by the presence of adult males, though young males expended less reproductive effort than adults. Instead, reproductive allocation occurred in a state-dependent manner, where pre-season levels of somatic reserves dictated reproductive effort, regardless of age. Like female ungulates, male deer displayed risk-sensitive reproductive allocation wherein current reproductive allocation occurred as a function of resources garnered during the prior season and were expended in a way that should have avoided over-investing and creating a tradeoff between reproduction and survival.